Implementasi Kebijakan Relokasi Pedagang Pasar Keputran Kecamatan Tegalsari Kota Surabaya - Kamilia Nur Afita (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
The aim of the research is to analyze the implementation of the trader relocation policy at Keputran Market, Tegalsari District, Surabaya City. This research uses a qualitative approach. The focus of this research is based on the Van Meter Van Horn theory to determine whether policies meet 6 indicators: policy standards and targets, inter-organizational communication and activity measurement, organizational characteristics of inter-organizational communication, attitude or character of implementers, social, political and economic resources and conditions. The location of this research is precisely in the Keputran Market area, Tegalsari District, Surabaya City. The research results show that the trader relocation policy is an attitude made by the Surabaya City government to create peace and order in the Keputran Market area because the traders carry out buying and selling on the shoulder of the road and the location is a public facility area. The implementation of existing policies at Keputran Market has not been carried out well by traders because there are still many traders who buy and sell on the sidewalk. Satpol PP has tried to control the Keputran Market area as much as possible, but there are still traders who do not follow the existing rules. The lack of knowledge of traders regarding the regulations of PERDA Number 1 of 2023 concerning Trade and Industry has caused obstacles to the implementation of the regulations that have been given by the government not to sell along the Keputran Market sidewalk.